(untitled) (Research, Society and Development, 2022)
Cowpea is an excellent food alternative for the population of northern Brazil. Although it presents resistance to pests and diseases and fixes atmospheric-N, inadequate practices can interfere with yield. The objective of this work was to evaluate the effect of water replacement in the soil based on field capacity moisture during the vegetative phase on cowpea production traits. The experiment was installed in a greenhouse, and the experimental design used was a randomized block with six treatments corresponding to the water replacement levels based on the field capacity moisture (0%, 20%, 40%, 60%, 80 % and 100%). The following parameters were evaluated: Number of pods per plant, average length of pods (cm), weight of pods, number of seeds per pod, weight of 100 grains (g) and grain yield (kg ha-1). Analysis of variance, regression and Tukey’s test were performed. The water deficit in the vegetative phase negatively affects the weight of grains and pods. Number of pods per plant, the weight of 100 grains and the total weight of pods increased linearly with increasing water supply. The highest number of grains per harvest was obtained when the soil was maintained at 60% of field capacity. The other differences do not differ significantly. Under the experimental conditions, the plants invested more in grain filling than in the number of plants and grains.